2008
DOI: 10.1038/oby.2007.29
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Quantitative Magnetic Resonance Method for Measuring Human Body Composition

Abstract: objective: To evaluate a novel quantitative magnetic resonance (QMR) methodology (EchoMRI-AH, Echo Medical Systems) for measurement of whole-body fat and lean mass in humans. Methods and Procedures:We have studied (i) the in vitro accuracy and precision by measuring 18 kg Canola oil with and without 9 kg water (ii) the accuracy and precision of measures of simulated fat mass changes in human subjects (n = 10) and (iii) QMR fat and lean mass measurements compared to those obtained using the established 4-compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
87
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 14 publications
10
87
3
1
Order By: Relevance
“…18 The authors concluded that the methodology will reduce the study duration and cohort number to evaluate anti-obesity interventions. The pediatric version of the QMR, as described in this study, is very similar in accuracy and precision of the measurements.…”
Section: Infant and Children New Body Composition Methods A Andres Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…18 The authors concluded that the methodology will reduce the study duration and cohort number to evaluate anti-obesity interventions. The pediatric version of the QMR, as described in this study, is very similar in accuracy and precision of the measurements.…”
Section: Infant and Children New Body Composition Methods A Andres Et Almentioning
confidence: 99%
“…QMR has been successfully used in small animals of different sizes (mice, rats and marmoset) [14][15][16][17] and in human adults. 18 QMR does not expose individuals to radiation, does not require immobilization and can span infancy through childhood, which makes it the most attractive technology for the estimation of body composition in the pediatric population. Owing to the similarity in size and composition, the pig has been widely used as a human model for validating methods of body composition measurement, including magnetic resonance imaging, 19 computer-assisted tomography 20 and most notably DXA.…”
Section: Introductionmentioning
confidence: 99%
“…Success in using QMR in animals of different sizes (flies, mice, rats, birds, dogs, pigs, infants, children, and adult humans) has been comprehensively reported (17)(18)(19)(20)(21)(22). This study addresses its potential for infants, using piglets as a generally accepted research model for infant body composition (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, this system generates a signal that modifies the spin patterns of hydrogen atoms within the subject and uses an algorithm to evaluate the resulting T1 and T2 relaxation curves specific to each of the four components measured: fat mass (FM), lean muscle mass equivalent, TBW, and free water. Each component is estimated based on an individually derived T1/T2 relaxation curve fractionated from the total returned signal.Success in using QMR in animals of different sizes (flies, mice, rats, birds, dogs, pigs, infants, children, and adult humans) has been comprehensively reported (17)(18)(19)(20)(21)(22). This study addresses its potential for infants, using piglets as a generally accepted research model for infant body composition (23,24).…”
mentioning
confidence: 99%
“…An important benefit of multislice image acquisitions is that the volumes of various tissues can be derived, thus eliminating the restrictions imposed by observations based on a single image. 33 Moreover, the concept of 'visceral adipose tissue' as a single compartment is advancing to the recognition of the existence of many anatomically localized depots with unique metabolic activities such as those located in bone marrow, epicardial area, around the kidneys (that is, peri and para-renal), and in the retro-orbital space. 34 Although some of these compartments can be directly visualized and therefore segmented into their component areas, in some cases contiguous adipose tissue compartments cannot be easily identified as to their origin.…”
Section: Imaging Methods Development Sb Heymsfieldmentioning
confidence: 99%